Manufacturing Axle Pulleys for Conveyor Belts from ST40 Iron: Proses Pembuatan Pulley Poros dari Besi ST40 - Baihaqi, Mukhammad Imam; Tjhajanti, Prantasi Harmi (Universitas Muhammadiyah Sidoarjo, 2024)
This study explores the production enhancements of St40 iron conveyor axles and pulleys, focusing on processes from design to finishing. Methods include material selection, precision machining, and protective treatments, leading to significant improvements in durability and performance in harsh environments. Results indicate potential for major impacts on the durability and reliability of global conveyor systems. Highlights : Precision Machining: Ensures high accuracy and consistency in axle and pulley production, critical for optimal conveyor performance. Heat Treatment: Enhances the mechanical properties of axles and pulleys, significantly increasing their resistance to harsh operational conditions. Protective Treatments: Applies advanced coatings to protect against wear and corrosion, extending the lifespan of conveyor components in severe environments. Keywords: Conveyor Durability, Precision Machining, Material Selection, Heat Treatment, Industrial Applications